KIAA0101 promotes cisplatin resistance through regulating cell apoptosis in lung cancer cells: KIAA0101 promotes cisplatin resistance - Zhang, Cian; Liu, Yongying; Zhao, Jing; Xu, Jingyu; Pei, Bei; Liu, Xuan; Yue, Xiaoqiang (Cellular and Molecular Biology, 2023)
Lung cancer is one of the most server mortality in the world and remains a huge threat to human health. Recently, cisplatin-based chemotherapy represented a common therapeutic strategy, however, cisplatin resistance greatly limits the therapy efficacy. We investigated whether KIAA0101 plays a role in cisplatin resistance of lung cancer cells and its mechanisms of action. The expression of KIAA0101 was evaluated based on comprehensive bioinformatic analysis. KIAA0101 knockdown and overexpression A549 cells were constructed to investigate its effects on cell proliferation and apoptosis induced by cisplatin treatment. Western blot analysis was performed to measure the levels of p53-related apoptosis proteins. We found that KIAA0101 was greatly increased in lung cancer tissues and cells. Knockdown of KIAA0101 suppressed cell proliferation and increased cisplatin-induced apoptosis. Knockdown of KIAA0101 also augmented the cisplatin-induced cell apoptosis signaling pathway. Then p53 was found to account for the role of KIAA0101 in cisplatin resistance. In conclusion, our findings provide a novel factor of KIAA0101 in lung cancer resistance, which suggests as a novel target for lung cancer therapy.